Penerapan Metode Problem Solving Learning pada Pelajaran Ekonomi Materi Pendapatan Nasional pada siswa kelas XI SMAN 5 Kabupaten Halmahera Utara - Pontoh, Adel (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to improve students' problem-solving abilities in learning economics subjects with national income material in class The research method used in this research is classroom action research. This classroom action research was carried out in two cycles, each cycle consisting of two meetings. At the end of each cycle, students are given a problem-solving ability test. The instruments used to collect data in this research were observation sheets, tests, questionnaires and interviews. Data analysis in this action research uses simple statistics, namely descriptive analysis. Descriptive analysis is an analysis model by comparing the average percentages. The results of the research show that there has been an increase in students' problem-solving abilities through the application of problem-based learning methods. Based on the results of observations, learning activities before using this learning method, the results of the final pre-cycle test showed that the number of students who experienced learning completion was 37.93%. This result shows that there are many obstacles and shortcomings. After learning was carried out using the problem based learning method, students' problem solving abilities increased, namely the average score obtained in cycle I increased to 75.86% and in cycle 2 it was 100%. Likewise, each indicator has increased. The results of the questionnaire analysis obtained in cycles I and II obtained a score in the good category. Based on the analysis of research data, there was an increase in learning completeness in cycle 1, 22 students were obtained and in cycle 2 there were 29. This shows that the application of problem based learning methods has an impact on increasing learning outcomes in economics subjects.